Kebijakan PPnBM: Menilai Keseimbangan Antara Insentif Mobil Listrik Impor dan Perlindungan Industri Mobil Lokal - Lestari, Tia; Samrotul Zanah, Shofa; Hidayat, Rahmat; Rahmawati, Vivi (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
The Sales Tax on Luxury Goods (PPnBM) policy can play a strategic role in supporting the transition to the use of electric vehicles as part of efforts to reduce carbon emissions and dependence on fossil fuels. This article assesses the balance between providing PPnBM incentives for imported electric cars and protecting the local car industry. This research uses the Literature Review method where this research uses a qualitative approach with policy analysis and secondary data from various sources, including government regulations, industry reports, and electric vehicle sales data. The research results show that the PPnBM incentive policy for imported electric cars has succeeded in increasing the adoption of electric vehicles, but has also posed serious challenges to the curiosity of the domestic electric car industry. This article recommends adjustment policies, such as incentive incentives for local manufacturers, an electric vehicle production development ecosystem, and incentive incentives for certain imported products. This step is expected to create a balance between environmental goals and locally based economic development.